Effect Of Drying Process To The Dimension Of Machined Core - Nik Mohamed Nasir, Nik Mohamed Syauqi (2015)
The continuous demands for low-weight structures ensure that honeycomb sandwich construction have many advantages. In aircraft industry, generally the honeycomb core can be divided into two types which are Nomex Honeycomb core and Kevlar Honeycomb core. To process honeycomb core, it is crucial to ensure the honeycomb core need to be dried first. The drying process was done in order to remove the moisture content in the honeycomb core. The drying is done by using drying oven with required temperature and duration. These projects focus to study the core that dried in drying oven at 120oC for 2 hours minimum because it was used in current production. This project was conducted to investigate the characteristic of the honeycomb core. To prove what happen to honeycomb core that after been dry whether it expand or shrink at which area. For RD of 200mm, NRD 400mm and RD of 400mm, NRD 200mm, Nomex and Kevlar core shows no significant effect in terms of dimension when exposed to environment for 2 hours and 12 hours. For RD of 200mm, NRD 400mm and RD of 400mm, NRD 200mm, Nomex core shows same effect in terms of dimension which both RD and NRD shrink when drying for 2 hours and 12 hours. For RD of 200mm, NRD 400mm and RD of 400mm, NRD 200mm, Kevlar core shows same effect in terms of dimension which both RD shrink and NRD expand when drying for 2 hours and 12 hours.